Diagnosis and therapy of myasthenia gravis—the patients’ perspective: a cross-sectional study - Sobierajski, Tomasz; Lasek-Bal, Anetta; Krzystanek, Marek; Gilhus, Nils E. (Frontiers in Neurology, 2023)
The survey aimed to explore patients’ perspectives with myasthenia gravis (MG) toward the diagnosis made and the therapy used to treat MG. The survey was conducted with a quantitative method, using the CAWI technique. A total of 321 people participated in the survey. More than half of the respondents (56.4%) had suffered from MG for less than 10 years. In three out of 10 cases (30.9%), the diagnosis of MG lasted 3 years or longer. The diagnostic delay was significantly longer in female respondents than in the males (p = 0.029). Cholinergic drugs were used in 92.9% of cases initially, and as maintenance therapy in 84.3% of cases. Corticosteroids were used in initiating therapy (45.8%) and as maintenance therapy (46.4%). One in four respondents (25.5%) reported experiencing very strong and strong side effects after using steroids. The side effects from steroid therapy very strong or strong affected overall physical health in 55.9% of respondents, very strong or strong affected self-acceptance in 52%, to a very large or large extent on mental health in 47.1%, and to a very strong or strong extent influenced the performance of daily activities in 28.2%. More than half of the respondents (57.0%) had had a thymectomy. Seven out of 10 respondents (72.0%) declared that the therapy they were on at the time of the survey allowed them (to varying degrees) to control their course of MG. Low therapy acceptance and less well controlled MG was associated with a preference for non-tablet therapies (p = 0.045). Regular follow-up and cooperation with the specialist health care system should improve MG symptoms, activities of daily living, and quality of life.